Differences in kinematics, kinetics, and muscle activity between underwater dolphin kicking and flutter kicking: multiple approaches using three-dimensional motion analysis, electromyography, and hydrodynamic simulation - Kobayashi Yamakawa, K.; Homoto, K.; Nakashima, M.; Shimojo, H.; Nakazono, Y.; Sengoku, Y.; Takagi, H. (Sports Biomechanics, 2025)
It is well-known among swimmers and coaches that the swimming speed of the underwater dolphin kick (UDK) is higher than that of the underwater flutter kick (UFK). This study aimed to clarify the differences in swimming performance between the two kicking styles in terms of kinematics, kinetics and muscle activity. Eight male swimmers performed UDK and UFK in a water flume at same effort levels. The three-dimensional motion analysis and measurement of surface electromyography for the left lower limb were performed. The fluid forces acting on the body and joint torques were estimated using Swumsuit simulator. As the results, the kick amplitude and range of joint motion were smaller for the UFK than for the UDK, and the muscle activity and the peak joint torques of the hip and knee were lower for the UFK than for the UDK. Furthermore, the estimated propulsion for both the downward and upward kicks was lower for the UFK than for the UDK. Therefore, our results suggest that the differences in propulsion between the two kicking styles, caused by the differences in movement and muscle activity, may influence the differences in swimming speed.